The Unity of Human Existence in the Light of Gadamer’s Philosophical Hermeneutics - Nyczak, Artur (Sensus Historiae, 2020)
The paper investigates the issue of historicity of existence and self-understanding within Gadamer’s philosophical hermeneutics. The purpose of the paper is to answer the question of how the author of Truth and method argues and interprets the unity of existence in the context of recognizing historicity as the fundamental characteristics of human being and the world. The paper shows that the historicity excludes the possibility of basing this unity on an absolute metaphysical foundation or on a reflective self-consciousness of transcendental subjectivity. On the ground of philosophical hermeneutics, being-one of a human has the character of historical continuity, constituted in the process of incessant, interpretive transcending and uniting oneself. The paper shows what roles the inherited tradition and community in which one lives play in this process. Furthermore, the paper points out that for proper understanding of Gadamer’s interpretation of the unity of existence, it is necessary to take into account two issues: firstly, its departure from the concept of empty time, which is a stream of the past, present and future moments of the “Now”, in favour of ful-filled time and secondly, how general-individual relations are interpreted in philosophical hermeneutics.